Origami for fun! - Berry, Thiranut Deborah (Minneapolis, Minn. : Compass Point Books, 2006)
Explains what origami is and provides paper folding instructions for making a variety of shapes.
Basics: Introduction: Origami for everyone! -- History: Folding formal to fun -- Origami paper: Which paper to use -- Understanding diagrams: Follow the directions -- Basic folds: Mountains and valleys -- Doing it: Simple origami bases: Covering your bases -- Project one: Snake -- Project two: Masu box -- Project three: Origami photo album -- Project four: Samurai helmet -- Project five: Boat -- Project six: Cicada -- Multiple-piece origami: Making a scene -- People, places, and fun: Sharing patterns: Pass the paper -- Origami by children: For kids only! -- Origami for peace: 1,000 cranes -- Paper worlds: Welcome to Oriland! -- Complex origami: It's all in the math! -- Famous folders: Who's made history in origami? -- Timeline: What happened when? -- Trivia: Fun origami facts -- Quick reference guide: Origami words to know -- Glossary: Other works to know -- Where to learn more -- Index.
IG1010L
Keywords: Origami